Penerapan Media E-book Interaktif Melalui Pendekatan CRT untuk Meningkatkan Hasil Belajar Matematika Kelas V di SDN Munggut 03 Kabupaten Madiun - Dayinta Qurota Ayunin; Pinkan Amita Tri Prasasti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The large number of students who are less motivated in learning mathematics results in a decline in students' mathematics learning outcomes. Therefore, several strategies and learning models are needed that can meet the needs of students. This study aims to optimize the mathematics learning outcomes of fifth grade students of SDN Munggut 03 by implementing e-book media with the CRT approach. In simple terms, e-books can be defined as electronic books or digital books. While the CRT approach is a learning approach that offers a meaningful learning experience, where students gain recognition and appreciation for cultural diversity and its integration with learning materials. This study used the PTK (Classroom Action Research) method where there were 2 research cycles. Data were collected through test, observation and documentation techniques. The results showed that the application of e-book media adapted to the cultural context (CRT) was effective in significantly increasing participation, motivation and mathematics learning outcomes in fifth grade students of SDN Munggut 03, Madiun Regency.